Emotional intelligence and family functioning in teeneger high school students - Zela Bravo, Raúl Stifp (2022)
Objective: To determine if there is a significant relationship between emotional intelligence andfamily functioning in teeneger high school students. Methodology: Quantitative approach, of adescriptive correlational type and has a non-experimental, cross-sectional design. The population is530 adolescents from 12 to 17 years old, students of the secondary level of a private school in Juliaca,Puno. The sample was confirmed by 320 participants, obtained through a non-probability conveniencesampling. The evaluation instruments were: The Emotional Intelligence Scale - WLEIS and the FACESIII Family Functionality Scale. Results: About 95% of the students present between average and highlevels of emotional intelligence, likewise 70% of the students perceive a healthy degree of cohesionand family adaptability and 30% perceive deficiencies and conflicts in their functionality family. On theother hand, the correlation of both variables was carried out through Spearman’s rho coefficient, whereit is appreciated that there is a moderate direct significant correlation between Family Functioning andEmotional Intelligence in adolescent high school students in general ( r = .465 **, p = .000) and withtheir respective dimensions. Conclusion: The higher the perceived family Functionality, the higher thelevels of Emotional Intelligence the adolescent will develop.